Manajemen Pengembangan Kompetensi Profesional Guru dalam Pencapaian Standar Nasional Pendidikan pada Madrasah Ibtidaiyah Negeri 26 Syamtalira Bayu Kabupaten Aceh Utara - Maulana Ilham (Medan Resource Center, 2024)
This study examines the management of teachers’ professional competency development in achieving the National Education Standards at Madrasah Ibtidaiyah Negeri Twenty Six Syamtalira Bayu, North Aceh Regency. It addresses how managerial practices shape competency development, the challenges encountered, and the extent to which such practices contribute to educational quality. A qualitative case study design was employed, with data collected through observations, semi-structured interviews, and document analysis involving the principal, vice principal, and teachers. The findings indicate that professional competency management has been implemented through systematic processes of planning, instructional delivery, and evaluation, supported by the use of learning media, educational technology, and communicative interaction with students. Several constraints persist, including limited teacher participation in professional training, insufficient capacity in developing instructional tools, and weaknesses in implementing and utilizing evaluation results. Teachers demonstrate strong social and communicative competencies that foster constructive relationships with students, parents, and the broader community. The study argues for the strengthening of needs-based management, the cultivation of a sustained professional culture, and the optimization of social capital to enhance educational quality.